D‐canavanine affects peptidoglycan structure, morphogenesis and fitness in Rhizobiales. (4th May 2021) - Aliashkevich, Alena; Howell, Matthew; Brown, Pamela J. B.; Cava, Felipe
Summary: The bacterial cell wall is made of peptidoglycan (PG), a polymer that is essential for maintenance of cell shape and survival. Many bacteria alter their PG chemistry as a strategy to adapt their cell wall to external challenges. Therefore, identifying these environmental cues is important to better understand the interplay between microbes and their habitat. Here, we used the soil bacterium Pseudomonas putida to uncover cell wall modulators from plant extracts and found canavanine (CAN), a non‐proteinogenic amino acid. We demonstrated that cell wall chemical editing by CAN is licensed by P. putida BSAR, a broad‐spectrum racemase which catalyses production of dl ‐CAN from l ‐CAN, which is produced by many legumes. Importantly, d ‐CAN diffuses to the extracellular milieu thereby having a potential impact on other organisms inhabiting the same niche. Our results show that d ‐CAN alters dramatically the PG structure of Rhizobiales (e.g., Agrobacterium tumefaciens, Sinorhizobium meliloti ), impairing PG crosslinkage and cell division. Using A. tumefaciens, we demonstrated that the detrimental effect of d ‐CAN is suppressed by a single amino acid substitution in the cell division PG transpeptidase penicillin binding protein 3a. Collectively, this work highlights the role of amino acid racemization in cell wall chemical editing and fitness.